2022
DOI: 10.3390/ijerph191912841
|View full text |Cite
|
Sign up to set email alerts
|

Association between Physical Fitness, Physical Activity Level and Sense of Coherence in Swedish Adolescents; An Analysis of Age and Sex Differences

Abstract: Introduction: The aim of this study was to investigate the association between physical fitness, physical activity, and sense of coherence (SOC) in Swedish adolescents (n = 2028 males, n = 1287 females) aged 14 to 18 using a cross-sectional design. Methods: Using the Swedish Physical power Mental harmony and Social capacity (FMS) student profile, participants performed physical tests measuring their cardiovascular ability (CV) and muscular strength. Questionnaires were used to measure physical activity levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
1
0
1
Order By: Relevance
“…The results of our study revealed a tendency for older students to be less physically active. The results of other research also have shown age-dependent physical activity and indicated a decrease in PA in students during adolescence [53][54][55] and especially during the pandemic period [49,[56][57][58]. A study conducted by Troiano's [59] team indicated that 42% of children aged 6-11 years in America met the recommended 60 min per day PA norm, whereas only 8% of adolescents reached this norm, and similar data were found in Australia [60].…”
Section: Discussionmentioning
confidence: 65%
“…The results of our study revealed a tendency for older students to be less physically active. The results of other research also have shown age-dependent physical activity and indicated a decrease in PA in students during adolescence [53][54][55] and especially during the pandemic period [49,[56][57][58]. A study conducted by Troiano's [59] team indicated that 42% of children aged 6-11 years in America met the recommended 60 min per day PA norm, whereas only 8% of adolescents reached this norm, and similar data were found in Australia [60].…”
Section: Discussionmentioning
confidence: 65%
“…Apesar das tendências naturais, as crianças tornaram-se menos aptas fisicamente nas últimas décadas [59,144]. Estudos observacionais em crianças e adolescentes, mostraram que as taxas de obesidade aumentaram enquanto que os níveis de aptidão física diminuíram, observando associações inversas entre as componentes da aptidão física e adiposidade [145,146]. Dados de pesquisas brasileiras apontaram uma prevalência de cerca de 40% das crianças com desempenho na aptidão física considerado fraco ou regular entre 2004 e 2015 [147,148].…”
Section: Aptidão Físicaunclassified